2014
DOI: 10.1155/2014/569319
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Techniques in Hip and Knee Arthroplasty: From the Daily Practice to Evidence-Based Medicine

Abstract: Total hip arthroplasty (THA) and total knee arthroplasty (TKA) are major orthopedic surgery models, addressing mainly ageing populations with multiple comorbidities and treatments, ASA II–IV, which may complicate the perioperative period. Therefore effective management of postoperative pain should allow rapid mobilization of the patient with shortening of hospitalization and social reintegration. In our review we propose an evaluation of the main analgesics models used today in the postoperative period. Their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 75 publications
0
25
0
1
Order By: Relevance
“…It has been concluded that analgesic needs are higher for patients undergoing knee replacement than those undergoing hip replacement. This means that patients undergoing hip replacement have less postoperative pain (Anastase et al 2014). It is possible that the smaller differences in our study are related to less pain, since new analgesia methods and operative techniques aimed at early mobilization and shorter hospital stay have been developed during recent years (Anastase et al 2014).…”
Section: Quality Of Recoverymentioning
confidence: 80%
See 2 more Smart Citations
“…It has been concluded that analgesic needs are higher for patients undergoing knee replacement than those undergoing hip replacement. This means that patients undergoing hip replacement have less postoperative pain (Anastase et al 2014). It is possible that the smaller differences in our study are related to less pain, since new analgesia methods and operative techniques aimed at early mobilization and shorter hospital stay have been developed during recent years (Anastase et al 2014).…”
Section: Quality Of Recoverymentioning
confidence: 80%
“…This means that patients undergoing hip replacement have less postoperative pain (Anastase et al 2014). It is possible that the smaller differences in our study are related to less pain, since new analgesia methods and operative techniques aimed at early mobilization and shorter hospital stay have been developed during recent years (Anastase et al 2014). It is also possible that the multi-centre, cross-cultural design might hide differences in QoR within and between the countries.…”
Section: Quality Of Recoverymentioning
confidence: 86%
See 1 more Smart Citation
“…LIA and FNB pain management methods are both used in TKA surgeries at the clinic. Multimodal analgesia was used in TKA and is critical for improvement of the rehabilitation and reduction of the hospitalization days [1,2,4]. Among these methods, FNB is considered as the gold standard because of its effectiveness [9].…”
Section: Discussionmentioning
confidence: 99%
“…Optimal perioperative analgesia will enhance functional recovery, including timely recovery of knee mobility, reduce length of hospital stay and reduce postoperative morbidity [1,2]. Thus, researchers recurrently study pain treatment of the surgery.…”
Section: Introductionmentioning
confidence: 99%